Respuesta :
The step by step multiplication is performed and shown below:
[tex](3x+2)(5 x^{2} -2x+6) \\ \\ =3x(5 x^{2} -2x+6)+2(5 x^{2} -2x+6) \\ \\ =15 x^{3}-6 x^{2} +18x+10 x^{2} -4x+12 \\ \\ =15 x^{3}+4 x^{2} +14x+12[/tex]
[tex](3x+2)(5 x^{2} -2x+6) \\ \\ =3x(5 x^{2} -2x+6)+2(5 x^{2} -2x+6) \\ \\ =15 x^{3}-6 x^{2} +18x+10 x^{2} -4x+12 \\ \\ =15 x^{3}+4 x^{2} +14x+12[/tex]
(3x + 2)(5x^2 - 2x + 6)
= (3x + 2)(5x^2 + - 2x + 6)
= (3x)(5x^2 ) + (3x - )(2x) + (3x )(6) + (2)(5x^2) + (2)( - 2x) + (2)(6)
= 15x^3 - 6x^2 + 18x + 10x^2 - 4x + 12
= 15x^3 + 4x^2 + 14x + 12
there you go...
= (3x + 2)(5x^2 + - 2x + 6)
= (3x)(5x^2 ) + (3x - )(2x) + (3x )(6) + (2)(5x^2) + (2)( - 2x) + (2)(6)
= 15x^3 - 6x^2 + 18x + 10x^2 - 4x + 12
= 15x^3 + 4x^2 + 14x + 12
there you go...